2010
DOI: 10.1080/00223891.2010.497423
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Values at an Early Age: The Picture-Based Value Survey for Children (PBVS–C)

Abstract: In this article, we introduce the Picture-Based Value Survey for Children (PBVS-C): a new assessment instrument that was developed within the conceptual framework of Schwartz's (1994) theory of universal human values. In the article, we describe the development of the PBVS-C with a specific focus on children's cognitive-developmental background (Harter, 1999; La Greca, 1990) and first applications. Multidimensional Scaling analyses in 2 samples of 8- to 12-year-old children (N= 267, N= 421, respectively) revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(140 citation statements)
references
References 26 publications
1
118
0
17
Order By: Relevance
“…The child then ranks the pictures according to the importance he or she ascribes to them. Across a range of studies, the PBVS-C showed to have good structural validity, as structural analyses yielded a clear distinction between the four higher-order values (Cieciuch, Davidov, & Algesheimer, 2016;Cieciuch, D€ oring, & Harasimczuk, 2013;D€ oring et al, 2010, 2015Uzefovsky et al, 2016). Multitrait-multimethod analyses of data from older children who were capable of completing an established values questionnaire for adults (the Portrait Values Questionnaire, PVQ, see below) in addition to the PBVS-C confirmed concurrent validity (Cieciuch et al, 2013;D€ oring et al, 2015): Correlations for the higher-order values measured across both instruments ranged from .42 to .72.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…The child then ranks the pictures according to the importance he or she ascribes to them. Across a range of studies, the PBVS-C showed to have good structural validity, as structural analyses yielded a clear distinction between the four higher-order values (Cieciuch, Davidov, & Algesheimer, 2016;Cieciuch, D€ oring, & Harasimczuk, 2013;D€ oring et al, 2010, 2015Uzefovsky et al, 2016). Multitrait-multimethod analyses of data from older children who were capable of completing an established values questionnaire for adults (the Portrait Values Questionnaire, PVQ, see below) in addition to the PBVS-C confirmed concurrent validity (Cieciuch et al, 2013;D€ oring et al, 2015): Correlations for the higher-order values measured across both instruments ranged from .42 to .72.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…The nature of prosocial behavior and underlying cognitive and motivational processes should vary across the lifespan. For example, whereas preschool children could show rudimentary forms of prosocial behavior and empathy that are not determined by moral considerations and values (30,31), adults could set long-term goals, engage in signaling behavior, and endorse values that help guide behavior (2, 9) and shape the social environment (23,24). Importantly, across levels of development low status should consistently increase prosocial behavior, the crucial adaptive strategy to low-status positions proposed here.…”
Section: Significancementioning
confidence: 99%
“…Study 4 was designed to this end. It focused on preschool children, an age before abstract representations, such as values, have started to form [which occurs at 7-8 y of age (31)]. Hierarchies in children up to the age of 7 are based on coercion and revolve around disputes about property ownership and other forceful behaviors (48).…”
Section: Studymentioning
confidence: 99%
“…Moreover, the basic human values theory of Schwartz has been used for studying values of children (Bilsky et al, 2013;Döring, 2010). Bilsky et al (2013) have also studied the structure of children's values and their value preferences, and have found in their results that children's value preferences are similar to the values of adults.…”
Section: Introductionmentioning
confidence: 99%